An assessment of the training needs of the library group in the National Library a projected human resources development plan - Macaspac, Gracia A. (1986)
This study attempts to identify the perceived training needs of The National Library group, their educational qualifications and the actual duties and responsibilities they perform so as to come up with a human resource development program for them.